Unique characteristics of the Ainu population in Northern Japan - Timothy Adrian, Jinam; Hideaki, Kanzawa-Kiriyama; Itsuro, Inoue; Katsushi, Tokunaga; Keiichi, Omoto; Naruya, Saitou (Springer Nature Limited, 2015)
Various genetic data (classic markers, mitochondrial DNAs, Y chromosomes and genome-wide single-nucleotide polymorphisms (SNPs)) have confirmed the coexistence of three major human populations on the Japanese Archipelago: Ainu in Hokkaido, Ryukyuans in the Southern Islands and Mainland Japanese. We compared genome-wide SNP data of the Ainu, Ryukyuans and Mainland Japanese, and found the following results: (1) the Ainu are genetically different from Mainland Japanese living in Tohoku, the northern part of Honshu Island; (2) using Ainu as descendants of the Jomon people and continental Asians (Han Chinese, Koreans) as descendants of Yayoi people, the proportion of Jomon genetic component in Mainland Japanese was ~ 18% and ~ 28% in Ryukyuans; (3) the time since admixture for Mainland Japanese ranged from 55 to 58 generations ago, and 43 to 44 generations ago for the Ryukyuans, depending on the number of Ainu individuals with varying rates of recent admixture with Mainland Japanese; (4) estimated haplotypes of some Ainu individuals suggested relatively long-term admixture with Mainland Japanese; and (5) highly differentiated genomic regions between Ainu and Mainland Japanese included EDAR and COL7A1 gene regions, which were shown to influence macroscopic phenotypes. These results clearly demonstrate the unique status of the Ainu and Ryukyuan people within East Asia.